HEALTH EXERCISES FOCUSED ON THE DEVELOPMENT OF STRONG PHYSICAL QUALITIES - Uraimov Sanjar Ruzmatovich; Qodirova Dilshoda Abdknabievna (Scholar Express Journal, 2022)
This article provides information on the health benefits of both types of strength training and the basic training tools used to develop strength training, such as lifting sports equipment, equipment and objects in a certain position, and keeping the body in a certain shape
Keywords: static endurance; dynamic endurance; maximum strength; speed-strength